Epigenetic priming with decitabine followed by low dose idarubicin and cytarabine in acute myeloid leukemia evolving from myelodysplastic syndromes and higher‐risk myelodysplastic syndromes: a prospective multicenter single‐arm trial. Issue 4 (24th June 2020) - Zhou, Xinping; Mei, Chen; Zhang, Jin; Lu, Ying; Lan, Jianping; Lin, Shengyun; Zhang, Yuefeng; Kuang, Yuemin; Ren, Yanling; Ma, Liya; Wei, Juying; Ye, Li; et al.
Abstract: Patients with acute myeloid leukemia (AML) evolving from myelodysplastic syndrome (MDS) or higher‐risk MDS have limited treatment options and poor prognosis. Our previous single‐center study of decitabine followed by low dose idarubicin and cytarabine (D‐IA) in patients with myeloid neoplasms showed promising primary results. We therefore conducted a multicenter study of D‐IA regimen in AML evolving from MDS and higher‐risk MDS. Patients with AML evolving from MDS or refractory anemia with excess blasts type 2 (RAEB‐2) (based on the 2008 WHO classification) were included. The D‐IA regimen (decitabine, 20 mg/m 2 daily, days 1 to 3; idarubicin, 6 mg/m 2 daily, days 4 to 6; cytarabine 25 mg/m 2 every 12 hours, days 4 to 8; granulocyte colony stimulating factor [G‐CSF], 5 μg/kg, from day 4 until neutrophil count increased to 1.0 × 10 9 /L) was administered as induction chemotherapy. Seventy‐one patients were enrolled and treated, among whom 44 (62.0%) had AML evolving from MDS and 27 (38.0%) had RAEB‐2. Twenty‐eight (63.6%) AML patients achieved complete remission (CR) or complete remission with incomplete blood count recovery (CRi): 14 (31.8%) patients had CR and 14 (31.8%) had CRi. Six (22.2%) MDS patients had CR and 15 (55.6%) had marrow complete remission. The median overall survival (OS) was 22.4 months for the entire group, with a median OS of 24.2 months for AML and 20.0 months for MDS subgroup. No early death occurred. In conclusion, the D‐IA regimen was effective and well tolerated, representing an alternative option for patients with AML evolving from MDS or MDS subtype RAEB‐2.